Comparative morphology of carnivorous plants, Utricularia minutissima and U. caerulae from Bintulu, Sarawak - A. I., Noorhawanie Izura; Bujang, Japar Sidik; Zakaria @ Ya, Muta Harah (Sarawak Biodiversity Centre, 2008)
The species of Utricularia are among the carnivorous plants which have complexity on their body morphology because there is no clear distinction between roots, stems and leaves. There is some confusion regarding this genus especially in Utricularia minutissima and U. caerulae because their morphological appearances are extremely similar. These plants can be divided into two sections; vegetative parts are usually on the ground and reproductive parts are very much visible above the ground. U. minutissima and U. caerulae showed similarities in their leaves, being green and aroused from the stolon which bears the bladder traps. These plants have no roots; instead, they have rhizoids which affixed the plant to the soil substrate. U. minutissima possessed lilac flowers and comprised of upper lip, lower lip, spur and calyx lobes. Fruit present in capsule and oblong-ovoid in shape with seeds are non-endospermic and have reddish reticulations on their surfaces. In contrast, U. caerulae possessed white flowers along inflorescence stalk in raceme fashion carrying one to six flowers. Fruit is a capsule globose in shape and seeds are brown with black edges, ellipsoidal in shape and have elongated reticulation at the surface.